Impact of the COVID-19 pandemic on the mental health of selected population groups - Chałupnik, Aleksandra; Borkowska, Aleksandra; Chilimoniuk, Zuzanna; Dobosz, Maciej; Wieteska, Małgorzata; Mizerski, Grzegorz (Journal of Education, Health and Sport, 2022)
Introduction and purpose: COVID-19 is a highly contagious disease that is caused by a new strain of SARS-CoV-2 coronavirus (type 2 acute respiratory syndrome virus). Globally, as of 14 July 2021, there have been more than 4 million deaths and almost 190 million confirmed cases of infection. Mental health disorders are sets of behaviours, ways of thinking or perceiving and other mental activities and relations with other people which are a source of suffering or impediments to the individual functioning of the affected person. The most common mental health disorders are anxiety disorders, insomnia, depression and somatic disorders. State of knowledge: The COVID-19 pandemic has disrupted people’s lives around the world through the rapid spread of the disease, high mortality and negative health effects. Over time, there is growing public concern that health systems may become overburdened and that adequate medical care will not be available to everyone affected by the disease. There are also concerns that isolation and reduced mobility will be long-term with serious consequences for mental health and well-being. Summary: There is already evidence of the negative psychological effects of the COVID-19 pandemic on children and adolescents, as well as the elderly who have been isolated, making these individuals more susceptible to developing long-term psychiatric disorders.